VALUE AND INFLUENCE OF BUDDHISM TO “KHMER-LOA KUI” WAY OF LIVES IN MOON RIVER, SURIN PROVINCE - Pariyatvisuttikhun, Dr; Jumnongruk, Itthipol; Kaewla, Wassana (PEOPLE: International Journal of Social Sciences, 2017)
This qualitative research aimed to study values and influences of Buddhism to ways of lives of Khmer-Laos-Kui’s communities in the Moon River, Surin Province. Three objectives of this study consisted of ways of lives, cultural relationship, and analyze the values and influences of Buddhism to the communities of Khmer-Laos-Kuis in the Moon River, Surin province. The research methods used were document studies. The data were collected from the research field, and in-depth interview from 21 informants. The results were as follows earlier ways of lives of Khmer-Laos-Kui’s communities living in the Moon River had different identities in language, culture, and tradition. Later, they had got close relationships, dependence in each other in living, learning, exchanging, economics, society, cultures, politics, and religious believes. These activities made them lived together in peace and harmony.The cultural relationships of Khmer-Laos-Kui’s communities in Surin province were classified into four aspects. They consisted of the moral aspect such as the belief in ancestral spirits and in Buddhism, the legal aspect such as the social orders by using ancient cultures and traditions, state laws, and Buddhist moral rules, the cohabitation aspect such as living in harmonious culture but being different in performing arts, such as, Kantrum folk music for Khmer, Isan Mor Lam traditional song for Laos, Kallmor Ritual for Kui, etc.,and the material aspect such as they had similarity in housing, constructions, dressing, and appliances.